التطور التشريعي والإداري للوقف الإماراتي في العصر الحاضر : دراسة تحليلية - كتبي، الفن مسعود راشد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The UAE has paid attention to Waqf (endowment) in two aspects, the first of which is the enactment of two endowment laws between 2011 and 2017 in the Emirate of Sharjah and the Emirate of Dubai, and the establishment of Waqf institutions to oversee Waqf activities in the country. This research aims to contribute to the development of the second version of the Federal Law of Endowment approved in 2018 (following few years of studying the bill) by finding out the best practices therein from which benefits can be derived. It also seeks to contribute to studying the case of institutional endowment management of the Dubai Foundation for Awqaf and Minors Affairs with a view to taking benefits from its practices that have contributed to a successful administrative work governance, and provision of other administrative practices aiming to develop the Waqf administrative work. This is achieved by researching the administrative and legislative nature of the United Arab Emirates' Awqaf in the past, and an evaluation of the governance of the main administrative systems in administering endowment foundations. Through inductive and analytical approaches, the researcher highlights the new Waqf's legislative and administrative visions. The research concludes with results the most prominent of which is that Waqf complies with the objectives of Sharia, and that Waqf activities were present throughout the history in the United Arab Emirates' ancient endowments. The states were also found as keen to establish institutions at the federal and local levels to support Waqf and follow up its affairs under a permanent governmental supervision. Moreover, the General Authority for Islamic Affairs and Endowments is found with utmost attention to the endowment legislation. The Awqaf and Minors Affairs Foundation is also found to have contributed to raising the level of its performance during years of work due to the government trend in evaluating the performance of institutions annually. The Awqaf and Minors Affairs Foundation has implemented working systems at the divisions' level, and methodologies for the most important operations, which have helped in governing the administrative process and supervising the performance.